Історія у боротьбі з югославізмом: Йосип Маль та його внесок у вивчення традиції словенської державності - Мальшина, К.В. (Історичний архів. Наукові студії, 2014)
Розглянуто розвиток словенської державотворчої ідеї в умовах Австро-Угорської
імперії та Держави СХС, виділено причини її несамостійності та прихильності
югославізму, зазначено важливі віхи біографії доктора Йосипа Маля, розглянуто його
головні твори та досліджено найважливіші висновки щодо основ словенського
державотворення, які засадничо вплинули на подальший розвиток національно-
політичної думки Словенії. Рассмотрено развитие словенской идеи государственного строительства в
условиях Австро-Венгерской империи и Государства СХС, выделены причины ее
несамостоятельности и приверженности югославизму, указаны важные вехи
биографии доктора Иосифа Маля, рассмотрены его основные работы и исследованы
важнейшие выводы относительно основ словенского государственного
строительства, которые основополагающе повлияли на дальнейшее развитие
национально-политической мысли Словении. Yugoslavism as the ideological and political movement in the Austro-Hungarian Empire has
emerged in the late XIX cent. and has been based on austroslavism or trialism. During the
whole period of its existence, until the end of the XX cent., it acquired various values depending
on the intra-imperial and international factors and, in turn, affected ethnic relations in the
Balkans. Its feature current was the mixing of the concepts of national idea, the civil idea, the
cultural-religious principles. For the vast majority of the Slavic politicians the national idea have
not yet become a political or state-building. Within Austria-Hungary during the global crisis and
World War I this idea has allowed Habsburgs’ Slavs to survive and to destroy the feudal empire.
In general, this mixing of the national, political and religious concepts indicates a very weak
development of the Balkan bourgeoisie, which in the early XX cent. could not nationally divided
in the confrontation with the Austrian bourgeoisie, already tight-knit by the German nationalism,
and after that in the First Yugoslavia – with the national unification.
The development of the Slovenian state-building thought went within the fight between
yugoslavism and slovenism. The Yugoslavism’s result was the collapse of the Austro-Hungarian
Empire, which certainly impacted positively on all aspects of life of its colonial peoples. But after
fulfilling its role as a catalyst of the national liberation, the idea didn’t came down from the
Balkan political arena, and after 1918 the Yugoslavism has only become the main contributing
factor to ethnic conflicts. For the leading Slovene People’s Party since the inception of the State
of SHS, and then the Kingdom of SHS/Yugoslavia, the experience of the political struggle within
the framework of the Austro-Hungarian Empire has cleared the fact: in a conflict of interests of
many nations in the united state the only way is the protection of the national idea and fight for
their own nation-state. But the particular state position of the Slovenian lands – which was
colonial during the last thousand years – have shown that this goal in terms of national
unification couldn’t be the achieved only by the Slovene bourgeoisie, which was small and
weak. It had to win by the support of the general public, which would be led by its intellectual
elite, who would propagand the scientific historical and ethnic studies, and especially evidences
of the "historicity" of the Slovene nation, the existence of its own nation-state and state-building
tradition.
Joseph Mal is the founder of the historical heritage of the Slovene State. He indicated the
formation of the princely power, the main administrative institutions as well as the existence of
Slovene legislation, mentioned in the sources as the Slovenes’ oath to their prince (Rota),
"Institutio Sclavenica" and "Slavica lex”, which proves the full compliance of Karantania to the
concept of "independent state". This evidences of the "historicity" of the Slovenes, despite the
opposition from the side of the ruling state internationalism, have gradually "ideologically 149
liberated" [15] the Slovenes from blinkers, concerning their own state past, and substantiated
the Slovenian national idea on the historical and legal basis.